PENGGUNAAN METODE “PERANG MENTAL MATEMATIKA” DENGAN MENGGUNAKAN MEDIA KARTU PECAHAN PADA MATERI PENJUMLAHAN BILANGAN PECAHAN - Indah Suciati (Fakultas Keguruan dan Ilmu Pendidikan, 2020)
Fractions are a subset of a set of real numbers. Although the form is simple and often used in everyday, but the material about fractions especially in the addition of fraction numbers is still complicated for students. To overcome this problem, a solution is given in the form of the method of